Survey of Red Fluorescence Proteins as Markers for Secretory Granule Exocytosis - Gandasi, Nikhil R. (PLoS One, 2015)
Fluorescent proteins (FPs) have proven to be valuable tools for high-resolution imaging studies of vesicle transport processes, including exo- and endocytosis. Since the pH of the vesicle lumen changes between acidic and neutral during these events, pH-sensitive FPs with near neutral pKa, such as pHluorin, are particularly useful. FPs with pKa>6 are readily available in the green spectrum, while red-emitting pH-sensitive FPs are rare and often not well characterized as reporters of exo- or endocytosis. Here we tested a panel of ten orange/red and two green FPs in fusions with neuropeptide Y (NPY) for use as secreted vesicle marker and reporter of dense core granule exocytosis and release. We report relative brightness, bleaching rate, targeting accuracy, sensitivity to vesicle pH, and their performance in detecting exocytosis in live cells. Tandem dimer (td)-mOrange2 was identified as well-targeted, bright, slowly bleaching and pH-sensitive FP that performed similar to EGFP. Single exocytosis events were readily observed, which allowed measurements of fusion pore lifetime and the dynamics of the exocytosis protein syntaxin at the release site during membrane fusion and cargo release.